The Influence Of Work Discipline And Organizational Culture On Employee Job Satisfaction In CV. Marnos Rattan Furniture - Rifky Manaf Fauzan (Al-Makki Publisher, 2023)
The purpose of this study is to determine the influence of work discipline and organizational culture on job satisfaction both partially and simultaneously. This research was carried out on CV. Marnos Rattan Furniture with 49 respondents. This study is an associative study. The data collection method in the implementation of this study used questionnaire tools that were distributed to employees as respondents. From the data obtained will be analyzed using the Likert scale method, then analyzed by validity tests, reliability tests, normality tests, multicollinearity tests, multiple regression analysis, coefficients of determination and hypothesis tests through t tests and f tests. It is partially known that the work discipline variable (X1) has a significant effect on the job satisfaction variable (Y) and the organizational culture variable (X2) has a significant effect on the job satisfaction variable (Y). Simultaneously, it is known that the work discipline variable (X1) and the organizational culture variable (X2) have a significant effect on the job satisfaction variable (Y) with an Adjusted R Square value of 0.257, meaning that the work discipline variable and the organizational culture variable together have an influence on the job satisfaction variable by 25.7%.